1332 թ. Սուրխաթի քառավետարանի նկարների համառոտ վերլուծությունը - Գայանե Բաբայան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
По воле судьбы, издавна армяне разбрелись по всему свету, создавая диаспоры в разных уголках мира. Одной из таких является Крым, где из-за нашествия арабов в VII веке, а затем сельджуков в XI веке и монголо-татаров в XIII веке, многочисленные армяне нашли убежище в Крыму и внесли значительный вклад в социально-экономическую, общественную и культурную жизнь Крымского полуострова. One of the most important Armenian colonies is the Crimea, where there are still preserved many Armenian architectural buildings and illustrated manuscripts. In the 7-13th centuries, because of political situation in Armenia - invasions, massive resettlement of Armenian population in the territory of the Byzantine Empire. Armenians found the shelter in the Crimea and made a significant contribution to the social-economic, public and cultural life of the Crimean Peninsula.
Keywords: Fine Arts; Painting